2013
DOI: 10.3390/molecules181114203
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Polyunsaturated Fatty Acids in Bone Development Using Animal Models

Abstract: Incorporating n-3 polyunsaturated fatty acids (PUFA) in the diet may promote the development of a healthy skeleton and thereby reduce the risk of developing osteoporosis in later life. Studies using developing animal models suggest lowering dietary n-6 PUFA and increasing n-3 PUFA intakes, especially long chain n-3 PUFA, may be beneficial for achieving higher bone mineral content, density and stronger bones. To date, the evidence regarding the effects of α-linolenic acid (ALA) remain equivocal, in contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 58 publications
(111 reference statements)
1
47
1
1
Order By: Relevance
“…[53] Differences also existed in the dietary fat source and composition between the Control (soybean oil) and HF (lard) diets, with both HF diets containing a higher saturated and monounsaturated fat and lower polyunsaturated n-3 (linolenic) and n-6 (linoleic) fatty acids (PUFA), which may affect bone development. [54,55] However, the above possibilities would likely affect cancellous and cortical bone in a directionally similar manner, which contrasts the divergent cancellous/cortical outcomes that we observed in HF animals.…”
Section: Discussioncontrasting
confidence: 54%
“…[53] Differences also existed in the dietary fat source and composition between the Control (soybean oil) and HF (lard) diets, with both HF diets containing a higher saturated and monounsaturated fat and lower polyunsaturated n-3 (linolenic) and n-6 (linoleic) fatty acids (PUFA), which may affect bone development. [54,55] However, the above possibilities would likely affect cancellous and cortical bone in a directionally similar manner, which contrasts the divergent cancellous/cortical outcomes that we observed in HF animals.…”
Section: Discussioncontrasting
confidence: 54%
“…The authors attributed this to the fact that calcium soaps of dietary unsaturated free fatty acids (oleic acid, C18:1) were absorbed by the bird as opposed to calcium soaps formed with saturated free fatty acids (palmitic acid, C16:0) in postpeak laying hens and broilers. Similarly, Lau et al (2010), Lau et al (2013) and Watkins et al (2000) observed consistent and reproducible beneficial effects of omega-3 fatty acids on bone metabolism and bone/joint diseases. Furthermore, Corwin (2003) found that high-oil diets, especially those rich in saturated fatty acids, may contribute to reduced bone density and increased fracture risk, in older as well as younger people.…”
Section: Bone Characteristicsmentioning
confidence: 64%
“…Importantly, ω 3 PUFAs have shown beneficial effects on bone health in animal studies [164, 165] but current research suggests only a modest increase in bone turnover in humans [166]. …”
Section: ω3 Long Chain Polyunsaturated Fatty Acids (ω3 Lc-pufas)mentioning
confidence: 99%